Chinese state capitalism and the international economic order - Che, Luyao (2017)
State capitalism, which refers to an economic system wherein the state maintains a guiding role in the economy based on the functioning of a market mechanism that is instrumental to the state, has experienced a rapid proliferation during recent decades. As a typical example of a state capitalist country, China has developed a highly institutionalised economic system characterised by a deep integration between the state and the market. This thesis aims to answer the questions as to how and why the rise of Chinese state capitalism has challenged the existing international economic order. It begins with an exploration of the ways in which Chinese state capitalism functions, submitting that the state simultaneously fulfils a triple role when intervening in the market, namely that of a planner, competitor, and a regulator. This research then doctrinally analyses the legal instruments adopted by China to advance its state capitalist practice, through which it argues that, compared to public law, private law has assumed greater importance in underpinning Chinese state capitalism. Next, by exploring both the world trading system and the international investment regime, the thesis contends that the international economic order has a limited ability to properly respond to the development of China’s state capitalism. The reason behind the limitation results from a failure to understand China’s contemporary state capitalism as an economic model that transcends the traditional market-state paradigm long-held by orthodox capitalism.